Theatre And Dance In Effe (1973-1982): The Feminist Magazine As An Archive Of Femininity And Corporeality (Itinera, 2019)
effe was the most important voice of Italian feminism during the Seventies. The magazine shared its premises with the feminist Teatro della Maddalena, in Rome, and dealt at large with women’s cultural production, including the performing arts — from theatre to dance, from happenings to community art. Through effe, the critique regarding woman’s body in the public sphere (a key-instance of the Women’s Movement) developed also through articles and chronicles about the stage. This essay argues that such discourse moved between two poles: the radical critique of the commodification of naked actresses on theatrical stages (pars destruens), and, on the other hand, the intellectual appreciation of dance as a site for a female reappropriation of woman’s body (pars costruens).